PENGARUH LEVERAGE, LIKUIDITAS, PROFITABILITAS, UKURAN PERUSAHAAN, UMUR PERUSAHAAN, DAN KUALITAS AUDIT TERHADAP KUALITAS LAPORAN KEUANGAN PERUSAHAAN - Zikri Aidilla Syarli (Bussman Journal : Indonesian Journal of Business and Management, 2021)
This study aims to test the effect of leverage, liquidity, profitability, firm size, firm age and audite quality on quality of financial reporting are measured by an index of accrual quality. The populations was wholesale and retail trade companies listed on the Indonesia Stock Exchange 2017-2019 period. Determination of the sample is done by using puposive sampling method based on secondary data from financial reports that are available in the Indonesia Stock Exchange website. There were about 225 companies selected at the sample of the study. The method of analysis used was multiple linear regression analysis. Liquidity, firm size, firm age and audite quality had effect on the quality of financial reporting. Leverage and Profitability had no effect on the quality of financial reporting